Management of problematic behaviours among individuals on long-term opioid therapy: protocol for a Delphi study - Merlin, Jessica S (BMJ Open, 2016)
INTRODUCTION: Given the sharp rise in opioid prescribing and heightened recognition of opioid addiction and overdose, opioid safety has become a priority. Clinical guidelines on long-term opioid therapy (LTOT) for chronic pain consistently recommend routine monitoring and screening for problematic behaviours. Yet, there is no consensus definition regarding what constitutes a problematic behaviour, and recommendations for appropriate management to inform front-line providers, researchers and policymakers are lacking. This creates a barrier to effective guideline implementation. Thus, our objective is to present the protocol for a Delphi study designed to: (1) elicit expert opinion to identify the most important problematic behaviours seen in clinical practice and (2) develop consensus on how these behaviours should be managed in the context of routine clinical care. METHODS/ANALYSIS: We will include clinical experts, defined as individuals who provide direct patient care to adults with chronic pain who are on LTOT in an ambulatory setting, and for whom opioid prescribing for chronic non-malignant pain is an area of expertise. The Delphi study will be conducted online in 4 consecutive rounds. Participants will be asked to list problematic behaviours and identify which behaviours are most common and challenging. They will then describe how they would manage the most frequently occurring common and challenging behaviours, rating the importance of each management strategy. Qualitative analysis will be used to categorise behaviours and management strategies, and consensus will be based on a definition established a priori. ETHICS/DISSEMINATION: This study has been approved by the Institutional Review Board (IRB) of the University of Alabama at Birmingham (UAB). This study will generate Delphi-based expert consensus on the management of problematic behaviours that arise in individuals on LTOT, which we will publish and disseminate to appropriate professional societies. Ultimately, our findings will provide guidance to front-line providers, researchers and policymakers.